Gibalna učinkovitost mestnih, primestnih in podeželskih otrok - Matejek, Črtomir (Revija za elementarno izobraževanje, 2008)
The main aim of the research was to find out whether there are any differences in physical fitness between children from urban, suburban and rural areas. The research was carried out on 451 children, aged from six to nine years. Among these children, 176 were from urban areas, 147 from suburban areas and 128 from rural areas. The children were from three different elementary schools in the northeastern part of Slovenia. In order to assess their physical fitness levels, six different tests were given in the following categories: explosive power, balance, visualmotor coordination, speed of alternate movements, whole-body coordination and endurance. The ANOVA method was used to asses the differences in physical fitness levels between children from different backgrounds. The statistical significance level was set at p<0.05. The differences were then defined more precisely using the Scheffe post-hoc test. Our results show that there are statistically significant differences between the children from different backgrounds in all the tested areas except balance. We have established that the children from urban areas achieved a higher level of physical fitness than children from suburban and rural areas. The differences are most likely due to many different factors, but among the most important are the socio-economic and cultural differences between urban, suburban and rural areas.
Keywords: sport; šport; gibalni razvoj; otroci; child; gibalna aktivnost; gibalne sposobnosti; bivalno okolje